mLogic: ultra-low voltage non-volatile logic circuits using STT-MTJ devices - Morris, Daniel; Bromberg, David; Zhu, Jian-Gang (Jimmy); Pileggi, Larry (DAC Design Automation Conference 2012, 2012)
This paper introduces the design of logic circuits based exclusively on novel magnetoelectronic devices. Current signals are steered by 2x resistance change switching while operating with sub-100 mV voltage pulses for power and synchronization. The inherent memory of the devices results in fully pipelined nonvolatile logic. We demonstrate that co-optimization of the devices, circuits and logic can achieve ultra-low energy-per-operation for design examples.